2019
DOI: 10.3390/polym11122074
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in Polyurethane Pre-Insulated Pipes

Abstract: The polyurethane foam in district heating pre-insulated pipes has a critical role to play both as thermal insulation and as load bearing element, as it serves as bond between the medium pipe and the casing. Hence, knowledge on how the foam behaves under multiaxial stresses is of great importance for the design as well as for aging predictions of the network. It is known that cell shape anisotropy in polymeric foams leads to anisotropy in its mechanical properties. In this study, we evaluate and quantify the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The foam is cyclopentane‐blown closed‐cell PU with an average density of 76.2 kg/m 3 . Details on the microstructural characterization have been presented in Doyle et al 23 The ends of the pipe samples were not sealed and in direct contact with air. However, previous research from accelerated ageing of PU pre‐insulated pipes under equivalent high ambient temperature have shown that changes in shear strength do not depend on the thermo‐oxidation of PU at the temperatures under consideration 24 and therefore this should not have a relevant impact on the obtained results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The foam is cyclopentane‐blown closed‐cell PU with an average density of 76.2 kg/m 3 . Details on the microstructural characterization have been presented in Doyle et al 23 The ends of the pipe samples were not sealed and in direct contact with air. However, previous research from accelerated ageing of PU pre‐insulated pipes under equivalent high ambient temperature have shown that changes in shear strength do not depend on the thermo‐oxidation of PU at the temperatures under consideration 24 and therefore this should not have a relevant impact on the obtained results.…”
Section: Methodsmentioning
confidence: 99%
“…22 In a previous work, we have found that PU in pre-insulated pipes presents a much higher anisotropy in both the microstructure and the mechanical properties under compression than that previously reported for PU slabs, arising from the different geometry of the mould during the foaming process. 23 This, together with the different geometry of the sample, an annular pipe, and the effect of high temperature, highlights the need for specific evaluation of this element.…”
Section: Fatigue and Fracture Of Pu Foam-state Of The Artmentioning
confidence: 99%
“…El suelo si bien contrarresta en parte los movimientos repentinos, se pueden generar condiciones de esfuerzos en las tuberías que alcancen niveles de fluencia. El comportamiento del aislante PUR bajo las condiciones extremas encontradas en tuberías de calefacción distrital está recién empezándose a investigar para conocer entre otros aspectos su respuesta termomecánica (Doyle et al, 2019;Banushi et al, 2021).…”
Section: Interacción Suelo-tuberíaunclassified